2020
DOI: 10.3847/2041-8213/ab63de
|View full text |Cite
|
Sign up to set email alerts
|

First Detection of the [O i] 63 μm Emission from a Redshift 6 Dusty Galaxy

Abstract: We report a ground-based detection of the [O I] 63-µm line in a z = 6.027 gravitationally lensed dusty star-forming galaxy (DSFG) G09.83808 using the APEX SEPIA 660 receiver, the first unambiguous detection of the [O I] 63 line beyond redshift 3, and the first obtained from the ground. The [O I] 63 line is robustly detected at 22±5 Jy km s −1 , corresponding to an intrinsic (de-lensed) luminosity of (5.4 ± 1.3) × 10 9 L . With the [O I] 63 /[C II] luminosity ratio of 4, the [O I] 63 line is the main coolant of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…A spectral stacking analysis of the data from the three non-detections reveals a significant signal, implying L [OI]63 µm = (1.1 ± 0.2) × 10 9 L . The line-to-total infrared luminosity ratio in BzK-21000 is similar to that of a dusty, z ∼ 6 galaxy (Rybak et al 2020), but lower than that typically observed in massive submm galaxies at z ∼ 1 − 3. Combined with PDR models, the relative strengths of the [OI]63µm and CO J =2-1 lines compared to the infrared luminosity imply a UV field intensity, G ∼ 320G 0 , and a gas density, n ∼ 1800 cm −3 .…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…A spectral stacking analysis of the data from the three non-detections reveals a significant signal, implying L [OI]63 µm = (1.1 ± 0.2) × 10 9 L . The line-to-total infrared luminosity ratio in BzK-21000 is similar to that of a dusty, z ∼ 6 galaxy (Rybak et al 2020), but lower than that typically observed in massive submm galaxies at z ∼ 1 − 3. Combined with PDR models, the relative strengths of the [OI]63µm and CO J =2-1 lines compared to the infrared luminosity imply a UV field intensity, G ∼ 320G 0 , and a gas density, n ∼ 1800 cm −3 .…”
Section: Discussionsupporting
confidence: 48%
“…The Herschel -PACS spectrometer enabled observations of the [OI]63 µm line emission in high-redshift, submm-selected starburst galaxies (Sturm et al 2010;Coppin et al 2012;Brisbin et al 2015;Wardlow et al 2017;Zhang et al 2018), which confirm the FIR line deficit observed in nearby luminous and ultraluminous galaxies. Most recently, Rybak et al (2020) have made a ground-based detection of [OI]63 µm in G09.83808, a dusty z∼6 galaxy, and from these data they infer a gas density, n = 10 4 cm −3 , and FUV field strength, G= 10 4 G 0 1 . To date, few observations of this line have been presented for lower redshift, main sequence star-forming objects like the BzK galaxies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nev ertheless, there hav e been many situations where simulations have agreed on emission-line properties of high-redshift galaxies and provide deep insights into or predictions of the early Univ erse. F or e xample, the necessary but insufficient condition that LyC leakers have high O32 (Barrow et al 2020 ;Katz et al 2020b ) as confirmed at z ∼ 2-3 (Nakajima et al 2020 ) or the strong [O I ] 63 μm (hereafter [O I ]) emission line (Olsen et al 2017 ;Katz et al 2019b ), that was recently observed at z > 6 (Rybak et al 2020 ).…”
mentioning
confidence: 88%
“…This value is unrealistic for a ground-based telescope, such as ALMA, and in principle could be achieved only by summing up the results of various observing runs of few hours each. As a matter of fact, the only detection of the [OI]63µm line available so far for a high-redshift galaxy is the one reported by Rybak et al (2020) for a strongly gravitationally lensed galaxy (magnification µ FIR 9) obtained with the APEX 12m telescope (Güsten et al, 2006), and the Swedish ESO PI (SEPIA) Band 9 receiver (Belitsky et al, 2018) 2020). We note that, while all reported detections have σ=5 or higher, the integration times can reach values of the order of 7.5 hrs.…”
Section: Predictions For Almamentioning
confidence: 99%